Pollination phenotypes in Phalaenopsis crosses: Guiding selection for optimal breeding - Bidarnamani, Fatemeh; mohkami, zeynab; karimian, Mohammad Ali (Journal of Horticultural Sciences, 2024)
Phalaenopsis orchid is one of the most popular flowers that have a large share of global flower and plant market due to its attractiveness, color varieties, and medicinal properties. In this study, the morphological (capsule length, full weight of capsule, empty weight of capsule, the weight of seeds in capsule and capsule volume) and phenological (time of pollination symptom, time of capsule swelling, and time of capsule ripening) traits of pollination were evaluated in 5 varieties of Phalaenopsis by the first plant pollination syringe of orchids in 5 types of self-pollination and 20 combinations of cross-pollination during 2019-2023. The results showed that 92% of the total variations were explained by the first 4 components in the analysis of the main components. The first and second components accounted for about 57.5% and 19.6% of the total data. Using cluster analysis results, pollination types were classified into three groups based on pollination factors. Discriminant analysis showed that clustering based on the Euclidean distance criterion was better than other distance criteria and was obtained favorably clustering based on it. Low heritability and genetic improvement were observed for time to petal wilting after pollination (TPS) characteristic. Nottingham × Nottingham pollination has the highest amount of capsule length, weight of seeds per capsule, capsule volume, and fresh weight of capsule. Capsule length had the most phenotypic and genotypic variation coefficient among all of the examined characteristics in 25 pollination types. The results of this study are used to select parents and favorable crosses to produce new varieties and capsules containing seeds.
Keywords: Capsule; discriminant analysis; orchid; pollination syringe; seed